2015
DOI: 10.1088/1367-2630/17/6/065005
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation theorem between non-equilibrium states in anRCcircuit

Abstract: Fluctuation theorems impose constraints on the probability of observing negative entropy production in small systems driven out of equilibrium. The range of validity of fluctuation theorems has been extensively tested for transitions between equilibrium and non-equilibrium stationary states, but not between general non-equilibrium states. Here we report an experimental verification of the detailed fluctuation theorem for the total amount of entropy produced in the isothermal transition between two non-equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…It has been shown that the injected power gives information about the interaction of the system with its surroundings [6,9,11,27], since it provides the necessary energy to sustain the system in a nonequilibrium steady state. In this case, P(ζ, V ) is the bivariate normal distribution of random variables ζ and V with zero means.…”
Section: Brownian Motion Analog Circuitmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the injected power gives information about the interaction of the system with its surroundings [6,9,11,27], since it provides the necessary energy to sustain the system in a nonequilibrium steady state. In this case, P(ζ, V ) is the bivariate normal distribution of random variables ζ and V with zero means.…”
Section: Brownian Motion Analog Circuitmentioning
confidence: 99%
“…Out-of-equilibrium experiments are a rich and active subject of study in Physics. Out-of-equilibrium experiments have involved the use of a wide range of systems under observation such as colloidal particles in optical traps [1][2][3], mechanical harmonic oscillators [4], turbulent flows [5,6], vibrating metallic plates [7,8], electrical circuits [9][10][11][12], DNA molecules [13,14], a gravitational wave detector [15] and granular media [16][17][18][19][20][21]. All of the previously mentioned experiments have measured the energy or power fluctuations of the system under out-ofequilibrium states and via its probability density function (PDF) with the goal of estimating system properties or testing theoretical findings [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The generating function (24), both for finite-time and periodic-NESS protocols with the duration or the period T can be written as follows…”
Section: Calculation Of P (W − ∆F )mentioning
confidence: 99%
“…Experimental verifications of dierent kinds of fluctuation relations have been initiated by measurements in biological systems [15] and then undertaken in various classical systems, such as mechanical [16][17][18], biological [19,20], and condensed matter systems both in contact with equilibrium [10,[21][22][23][24][25] and non-equilibrium [26] environments. In most of these systems, thermodynamic variables (work, heat, or entropy) have been extracted indirectly via the measurement of the microscopic state of the system (a position of the bead in a laser tweezer, an instantaneous angular deflection of the rotation pendulum, a charge state of a Coulomb-blockaded device and so on).…”
Section: Introductionmentioning
confidence: 99%
“…explored by Granger et al for an RC-circuit [17]. Alemany et al present data and theory on the modification of fluctuation theorems for partially equilibrated initial states of DNA-hairpins, closing with a perspective on thermodynamic inference based on partial experimental data [18].…”
mentioning
confidence: 99%